A measurement to analyze the relative change in the Absolute Parity of Power Purchase: An application to the European Union - Santiago Rodriguez Feijoo; Alejandro Rodriguez Caro; Carlos Gonzalez Correa (European Regional Science Association (ERSA), 2003)
In the present paper an index to measure the changes in the Absolute Purchasing Power Parity. in the short term of a group of territories that conform an unique market, using the information of the Harmonized Index of Consumer Prices and the Exchange Rates. This measurement is utilized to study the change in relative prices of the countries of the European Union for the period 1991-2002, and the fulfillment of the theory of the Relative Purchasing Power Parity, taking as a reference the Absolute Purchasing Power Parity in the reference time of the Price Index. The difficulties found to do these comparisons have given rise to multitude of jobs that can be classified in two large groups. In the first group are the efforts focused to find the best instrument to do comparable the figures of the distinct economies. In this line, it is emphasized the use and the advances in the index numbers theory [for a historic revision applied to price index see Diewert, W. (1993), for a theoretical revision see Balk, B. (1995) and Hill, T. (1988)] and the jobs carried out in the International Program of Comparison (ICP), program belonging to the statistical division of United Nations with near 35 years of life, and whose objective is to produce estimations of the National Gross Product and its components, that can be comparable among countries in real terms. It utilizes the concept of Purchasing Power Parity (PPP), [UN (1992)]. In the same line, the European Program of Comparison is developed by Eurostat and the OCDE since 1980. In the second group the investigations based in the unit price law and the theory of of the PPP to explain the behavior of the rate of change among two or more countries. In this case, the objective is focused in the analysis of the economic implications of its fulfillment or not, and how being able to test its fulfillment [Cheung, AND W., Lai, K. (2000), Engel, C. (2000), Reads, M. (1976), Taylor, A. (2001)] This job is inside of the first group of investigations. An index is defined to reflect changes in the Relative Purchasing Power Parity among a group of countries that do not share a common currency. This measurement can be obtained from Harmonized Index of Consumer Prices (HICP), and from the Exchange Rates among the currencies of the distinct countries. The results show the strong distorting effect that exchange rate has upon the Purchasing Power Parity among countries. The evolution of the internal prices of each country is a residual factor to explain the changes in the Purchasing Power Parity. In this sense, the apparition of euro contributes to a clear stability for the consumers whose countries have adopted the euro than those that have not adopted yet. However, in the euro zone systematic behaviours in some of the countries are detected that indicate that, their Purchasing Power Parity is changing in a systematic way, with regard to the average Purchasing Power Parity of the Monetary Union.
Keywords: 330